Biochemical, coagulation, and platelet count profiles among Schistosoma mansoni infected patients attending at selected Dembiya health institutions, Northwest Ethiopia - Wagaw Abebe; Wossenseged Lemma; Yalewayker Tegegne; Assefa Sisay; Tadesse Misganaw; Sisay Ayana; Desie Kasew; Marye Nigatie Debash; Alemu Birara Zemariam; Tadele Emagneneh; Adane Derso (BMC Microbiology)
Abstract Background Schistosomiasis is a parasitic disease that causes coagulation disorders and biochemical abnormalities. This is due to liver failure, platelet destruction, disruption of blood flow, and endothelial function by the schistosomes. However, there is no adequate data on biochemical and coagulation profiles and platelet count of patients infected with Schistosoma mansoni in Dembiya Selected Health Institutions. Hence, the aim of this study was to assess the effect of Schistosoma mansoni infection on selected biochemical and coagulation profiles and platelet count. Method An institutional-based comparative cross-sectional study was conducted from March to August 2022 at Dembiya Primary Hospital, Chuahit Health Center, and Abrija Health Center, Northwest Ethiopia. A total of 70 individuals were enrolled in the study using convenient sampling techniques. A stool sample was collected for Schistosoma mansoni detection. Likewise, a blood sample was collected for biochemical and coagulation profiles and platelet count analysis. The data were analyzed using SPSS version 25. A p-value less than 0.05 was considered statistically significant. Results Median values for alanine aminotransferase, aspartate aminotransferase, creatinine, total bilirubin, and direct bilirubin values were significantly higher, while total protein and glucose were significantly lower in Schistosoma mansoni infected than in the healthy control participants (P < 0.05). Prothrombin time, activated partial thromboplastin time, and international normalization ratio were significantly higher, while the platelet count was significantly lower in the Schistosoma mansoni infected than healthy control participants (P < 0.05). The values of alanine aminotransferase, aspartate aminotransferase, creatinine, total bilirubin, direct bilirubin, prothrombin time, activated partial thromboplastin time, and international normalization ratio were significantly higher, while total protein, glucose, and platelet count were significantly lower in those with moderate and heavy Schistosoma mansoni infection intensity compared to healthy control participants (P < 0.05). The number of Schistosoma mansoni eggs per gram of stool had a positive correlation with biochemical and coagulation profiles, except for total protein, glucose, and platelet count, which were correlated negatively in Schistosoma mansoni infected participants (P < 0.05). Conclusion Biochemical and coagulation profiles, including alanine aminotransferase, aspartate aminotransferase, creatinine, total bilirubin, direct bilirubin, glucose, total protein, prothrombin time, activated partial thromboplastin time, international normalization ratio, and platelet count, were significantly altered in S. mansoni infected participants compared to controls (p < 0.05). These findings underscore the need for routine biochemical and coagulation monitoring in endemic areas.